The Role of Chatbots in Mental Health Interventions: User Experiences - Saadati , Seyed Amir; Saadati, Seyed Milad (AI and Tech in Behavioral and Social Sciences, 2023)
This study aims to explore the user experiences of individuals interacting with mental health chatbots, identifying key themes related to engagement, efficacy, satisfaction, barriers, and potential improvements. The objective is to inform the design and implementation of chatbot interventions to better meet the needs of users seeking mental health support. A qualitative research design was employed, utilizing semi-structured interviews with 22 participants who have used mental health chatbots. Thematic analysis was conducted to extract major and minor themes from the transcribed interviews, focusing on the aspects of user interaction, perceived benefits, and areas for enhancement in chatbot functionality. Five major themes were identified: User Engagement and Interaction, Perceived Efficacy, User Satisfaction and Trust, Barriers and Limitations, and Future Directions and Improvements. These encompassed various categories such as ease of use, personalization, emotional support, privacy concerns, technological issues, and suggestions for advanced AI and better integration with professional care. Participants valued chatbots for their accessibility and personalized support but highlighted the need for improvements in emotional understanding and technical reliability. Mental health chatbots are a promising tool for supporting individuals with their mental health needs, offering benefits in terms of engagement, personalized support, and perceived efficacy. However, addressing identified barriers such as technological limitations and emotional disconnect is crucial for enhancing user satisfaction and trust. Future developments should focus on incorporating advanced AI technologies, ensuring user privacy, and integrating chatbots more closely with traditional mental health services.